Innovative 7E Learning Cycle E-Worksheets: Improving Fraction Learning and Numeracy Literacy in Elementary Students - Dyah Triwahyuningtyas; Cindy Nada Gisela; Nyamik Rahayu Sesanti (Universitas Pendidikan Ganesha, 2024)
Student worksheets in schools generally consist of printed evaluation sheets with limited instructions and no visual aids, leading to low reading comprehension and difficulty in understanding learning materials, particularly fractions. This study aims to develop a 7E Learning Cycle-based electronic worksheet that is valid, practical, and effective in improving the numeracy literacy skills of fourth-grade elementary school students. This research employed a developmental research method using the 4D model. The study involved 21 fourth-grade students in an elementary school. Data analysis techniques included both qualitative and quantitative approaches. Qualitative data were obtained through interviews, expert validation sheets, and student response questionnaires, while quantitative data were derived from validation tests and response questionnaires. The validation results showed that the electronic worksheet received a score of 99.47% from material experts and 97.72% from media experts, both categorized as highly valid. The effectiveness test, measured through pre-test and post-test results, indicated a significant improvement of 39.4 points, with an average N-gain score of 0.788, categorized as high. Student response questionnaires revealed that the electronic worksheet is highly practical. These findings demonstrate that the 7E Learning Cycle-based electronic worksheet on fractions is valid, practical, and effective in enhancing elementary school students' numeracy literacy skills.